Ingestion rates and grazing impact of the brackwater mussel Brachidontes virgiliae in Lake St Lucia, iSimangaliso Wetland Park, South Africa. Issue 2 (19th August 2016) - Nel, HA; Perissinotto, R; Carrasco, NK
Abstract : Bivalves feed on a combination of phytoplankton and zooplankton and have the potential to impact considerably the planktonic biomass, especially when they occur in high densities, such as in oyster and mussel beds. The brackwater mussel Brachidontes virgiliae is numerically dominant during wet phases within Africa's largest estuarine lake, St Lucia, in the iSimangaliso Wetland Park on the east coast of South Africa. The ingestion rates and potential grazing impact of this small mussel (maximum shell length = 2.5 cm) were estimated for both the wet and dry seasons using an in situ gut fluorescence technique. Ingestion rates were higher during the wet season (5.78 µg pigment ind. −1 d −1 ) than during the dry season (4.44 µg pigment ind. −1 d −1 ). This might be explained by the increased water temperature and food availability during the wet season. Because of the patchy distribution of mussel populations, there could be higher localised grazing impact near mussel aggregations. Results showed a potential grazing impact of up to 20 times the available phytoplankton biomass at specific sites. These high grazing impacts have the potential to deplete phytoplankton stocks in the lake, especially during wet phases in the northern reaches, where mussel densities are highest. This needs to be factored into ecological models of Lake St Lucia, because the system might function differently during increased flood events.